2016
DOI: 10.1016/j.ejbas.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic studies and thermal properties of PCL/PMMA biopolymer blend

Abstract: Available online A B S T R A C TPolycaprolactone/Polymethylmethacrylate (PCL/PMMA) biopolymer blend can be prepared by casting technique. Structural, optical and thermal properties of the blend have been studied using X-ray diffraction (XRD), infrared spectroscopy (FTIR), ultraviolet-visible spectroscopy (UV-Vis) and thermogravimetric analysis (TGA). XRD show two diffraction peaks at 2θ = 21.4°a nd 23.8°which attributed to the planes (110) and (200) that represent crystallographic planes of semi-crystalline PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
101
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(113 citation statements)
references
References 25 publications
(25 reference statements)
7
101
0
5
Order By: Relevance
“…A 2θ value of 8.10° has been reported for PMMA [21]. The weak background hump around 2θ = 42° has been observed in other works [2,22]. This 2θ value is also indicative of the amorphous nature of the material.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…A 2θ value of 8.10° has been reported for PMMA [21]. The weak background hump around 2θ = 42° has been observed in other works [2,22]. This 2θ value is also indicative of the amorphous nature of the material.…”
Section: Resultsmentioning
confidence: 58%
“…Lead discharged by several industrial and commercial activities is found in the environment, such that its removal, from water and wastewater has become a challenge to researchers [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of C=O groups of PCL represented in FTIR-ATR spectrum (Figure 2) at about 1730 cm −1 . However, no absorption peak at longer wavelength above 280 nm was observed[28]. PCL/P3ANA nanofibers exhibit new bands which are characteristic of P3ANA.…”
mentioning
confidence: 93%
“…As it is clearly seen, all three spectra are overlapping and can be compared in qualitative (signals position) and quantitative way (signals intensity). For PCL some of the characteristic bands [15]:…”
Section: Resultsmentioning
confidence: 99%